2015
DOI: 10.1039/c5fo00342c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary extra virgin olive oil and its fractions on antioxidant status and DNA damage in the heart of rats co-exposed to aluminum and acrylamide

Abstract: Oxidative stress generated by an excessive production of free radicals has been linked to the development of several health problems such as cardiovascular diseases. We investigated the protective efficacy of Extra Virgin Olive Oil (EVOO) and its lipophilic fraction (OOLF) and hydrophilic fraction (OOHF) against the cardiotoxicity and DNA damage induced by co-exposure to aluminum (AlCl3) and acrylamide (ACR). Rats were divided into eight groups of six each: controls, AlCl3 (50 mg per kg body weight) administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Co-administration of OOHF reduced the DNA damage via its strong anti-oxidant activity and thereby restores the DNA integrity of the lung cells. In our previous study, we have reported that EVOO and its hydrophilic and lipophilic fraction exerted a protective effect against Al and ACR treatment by reducing the smear formation in the heart of rats (Ghorbel et al 2015c). According to Dearfield et al (1988), among polyphenols, hydroxytyrosol (HT) is the most abundant polyphenol present in olive oil in free form or linked to the dialdehydic form of elenolic acid and considered as an isomer of oleuropein aglycon.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Co-administration of OOHF reduced the DNA damage via its strong anti-oxidant activity and thereby restores the DNA integrity of the lung cells. In our previous study, we have reported that EVOO and its hydrophilic and lipophilic fraction exerted a protective effect against Al and ACR treatment by reducing the smear formation in the heart of rats (Ghorbel et al 2015c). According to Dearfield et al (1988), among polyphenols, hydroxytyrosol (HT) is the most abundant polyphenol present in olive oil in free form or linked to the dialdehydic form of elenolic acid and considered as an isomer of oleuropein aglycon.…”
Section: Discussionmentioning
confidence: 97%
“…K 182001) as reported by Kiprianova et al (2011) and Ghorbel et al (2015c). To verify the extent of DNA damage in the lung, we performed the DNA smear technique.…”
Section: Dna Fragmentation Assay In the Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License the kidney and liver (Ghorbel et al, 2015). The molecular mechanisms include membrane function disruption, oxidative stress induction and disruption of several metals' metabolism (Hasona and Ahmed, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…GSH levels depleted in heart, decreased the permeability of membrane leading to leakage of enzymes creatine kinase and lactate dehydrogenase, their activities reflect the alterations in the heart. Histological examination of heart showed inflammation and marked vascular congestion [50].…”
Section: Singh and Kushwahmentioning
confidence: 99%